A Generation, or the Ordering of History – The Case of the Year 1968 in Poland - Czyżewski, Andrzej (Sensus Historiae, 2023)
The main object of this article is to examine to what extent the concept of generations applies to the Polish 68ers and their oral testimonies. To provide a deepened analysis of this problem, I divided my text into two major parts. In the first one, I drew both methodological and historical context of the ’68 generation controversy, including, for example, long-lasting discussions about the advantages and limitations of using “generation” as an analytical tool in social science and humanities. The second part of my article consists of the original analysis of oral testimonies — gathered mostly by myself — of the participants of the so-called “March events” from Łódź. Here I seek to find answers to such questions, for example, as: to what extent does the dominant narrative about the Polish ‘68 generation apply to more provisional circumstances? Is Mannheim's distinction between “generation” and “generation unit” a possible solution to a problem of different, and in many cases even opposing, generations rooted in the same historical events?